Disease control and quality of life in chronic spontaneous urticaria and recurrent angioedema are strongly linked, but not in all patients - Sophia Neisinger; Pascale Salameh; Annika Gutsche; Felix Aulenbacher; Frank Siebenhaar; Marcus Maurer (Clinical and Translational Allergy)
Abstract Background Patient‐reported outcome measures (PROMs) help to assess disease control and quality of life (QoL) in chronic spontaneous urticaria (CSU) and recurrent angioedema (RA). This study aimed to assess the correlation between two different concepts: disease control and QoL, using disease‐specific PROMs. Methods We analyzed data from 445 CSU and 330 RA patients who completed both a disease control and QoL PROM as part of the clinical routine. We included the UCT and CU‐Q2oL for CSU and AECT and AE‐QoL for RA. Results In CSU and RA, disease control scores positively correlated with QoL scores (Spearman's rho correlation coefficient (CR) −0.757, −0.735; p < 0.001) with better disease control corresponding to better quality of life. However, 5.9% of CSU patients and 28% of RA patients with complete disease control had impaired QoL. In CSU, QoL was impaired in 69.2% of patients based on the CU‐Q2oL and in 62.7% of patients based on a single numeric question from the UCT, with a mismatch in 89/445 patients. In RA, QoL was impaired in 58.5% using the AE‐QoL and in 52.7% using a single numeric question from the AECT30mo, with a mismatch in 69/330 patients. Different domains of the QoL PROMs showed different degrees of influence on disease control, with “Itching/Embarrassment” showing the strongest correlation with the UCT (CR −0.804; p < 0.001) and “Functioning” with the AECT3mo (CR −0.824; p < 0.001). Conclusion Although most patients with controlled disease have better quality of life, unexpectedly, quality of life remains impaired in up to one‐fourth of patients with completely controlled CSU and RA. Reasons behind this should be investigated in further studies.